Zur Verbreitung der Epermeniidae und Acrolepiidae auf der Iberischen Halbinsel (Lepidoptera). - Gaedike, Reinhard (Contributions to Entomology = Beiträge zur Entomologie, 1971)
A survey is given of the Epermeniidae and Acrolepiidae of the Iberian Peninsula. The study of the material and the evaluation of publications so far established 16 species of both families in this region. Nomenclatural Actsstaintonella (Millière, 1869) (Ochromolopis), change in authorship hitherto was Stainton (1869) the author